2012
DOI: 10.1371/journal.pone.0043925
|View full text |Cite
|
Sign up to set email alerts
|

Ratio between Negative and Positive Lymph Nodes Is Suitable for Evaluation the Prognosis of Gastric Cancer Patients with Positive Node Metastasis

Abstract: ObjectiveTo date, there is no consensus to evaluate the most appropriate category of the nodal metastasis for precise predication the prognosis of gastric cancer patients with positive node metastasis after curative surgery.MethodsWe retrospectively analyzed the clinicopathologic characteristics and overall survival (OS) of 299 gastric cancer patients with positive node metastasis after curative surgery for evaluation the optimal category of the nodal metastasis.ResultsWith the univariate and multivariate surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 37 publications
(36 reference statements)
2
9
0
Order By: Relevance
“…Nonetheless, some investigators demonstrated that both the 6th pN and 7th pN classifications were not the most appropriate cutoffs for number of positive nodes to predict the clinical outcomes of GC patients . LNR has been proposed as another promising classification, which was considered to be superior to pN classification in some retrospective studies .…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, some investigators demonstrated that both the 6th pN and 7th pN classifications were not the most appropriate cutoffs for number of positive nodes to predict the clinical outcomes of GC patients . LNR has been proposed as another promising classification, which was considered to be superior to pN classification in some retrospective studies .…”
Section: Discussionmentioning
confidence: 99%
“…The lymph node ratio (LNR), defined as the number of involved nodes divided by the number of lymph nodes examined, was found to improve prognostic information in breast cancer, gastric cancer, colorectal cancer, melanoma and others. [6], [7], [8], [9], [10], [11], [12] Approximately 60% to 80% of patients with hypopharyngeal cancer have locally advanced disease with spread to regional nodes at diagnosis. [13] However, there have been no previous studies on the impact of the LNR on predicting the prognosis of hypopharyngeal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Recently, we demonstrated that the ratio between negative and positive lymph nodes (R NP ) is associated with prognosis prediction for smallscale patients with positive lymph node metastasis. 11 To test the clinical applicability of R NP for prognostic prediction in GC, we designed this study to elucidate the most accurate prognostic predictor among N stage, R PD , and R NP for large-scale GC patients.…”
mentioning
confidence: 99%